Meta Study of the Relationship between Knowledge and Incentives with Posyandu Cadre Performance - Arjan Arkasi; Syamsul Arifin; Ari Yunanto; Eko Suhartono; Fauzie Rahman (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Posyandu cadre performance refers to the role of cadres in posyandu activities as inthe Posyandu cadre handbook, explaining the role of posyandu cadres is divided into three stages,namely before posyandu opening days, posyandu opening days and after posyandu opening days. Manystudies report different results on the performance of health cadres related to knowledge and incentives.The purpose of this paper is to analyze the relationship between knowledge and incentives with theperformance of posyandu cadres.Method: The research method used is meta-analysis to assess how big the effect of the knowledge andincentive variables will be on the performance of posyandu cadres.Result: Based on the results of the study of research articles, the combined P-value of 0,000 on theknowledge variable, and the combined p-value of 0,039 on the incentive variable.Conclusion: There is a relationship between knowledge and incentive variables on the performance ofposyandu cadres.